The Development of Animated Video Learning Media Using Animaker to Improve Students' Critical Thinking Skills - Nabila, Helmi Ilham; Kurniawan, Rudy; Hidayat, Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Along with the development of Information and Communication Technology, learning media is now increasingly diverse. Teachers must be smart in choosing the right media so that it can facilitate students in understanding the material presented. The purpose of this research is to develop animated video learning media using animaker that is feasible and practical to use in learning mathematics in the classroom. The research method used is the Research and Development (R&D) method. The research model uses the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects in the small-scale trial were 8 students of class XI MAN Kota Cimahi and in the large-scale trial were 24 students of class XII MA Misbahunnur. The data collection technique was carried out by distributing response questionnaires to students to see the average using Microsoft Excel. From the results of product research, the feasibility of the products developed in the small-scale trial was 75%. While in the large-scale trial of 93% so that it is included in the criteria is very feasible. The practicality results of the small and large trials obtained 87% which showed very practical criteria. For a significance value of 0.0005 <0.05, the critical thinking ability whose learning uses animated video learning media using animaker with a scientific approach is better than ordinary learning. Thus, animated video learning media using animaker on statistics material is feasible and practical to use as a medium for learning mathematics.